(untitled) (FUDMA JOURNAL OF SCIENCES, 2022)
This study was conducted to determine the amino acids content of some lima beans (Phaseolus lunatus) foods in Kaduna state, so as to provide nutritional basis for increased utilization of lima beans as a value-added product in households. The foods include lima bean porridge, lima bean-benniseed and lima bean-hungry rice. These foods were subjected to proximate and amino acids analysis using standard procedures and analytical methods. Amino acid composition of lima bean-benniseed recorded higher content of essential amino acids leucine (6.97g/100g), lysine (7.10g/100g), methionine (2.60g/100g), threonine (3.81g/100g), and also had higher content of non-essential amino acids, tyrosine (3.45g/100g), alanine (4.54g/100g), serine (3.94g/100g), glutamic acid (12.94g/100g) and aspartic acid (8.68g/100g). Lima bean-hungry rice food had higher content of isoleucine (4.04g/100g), phenylalanine (4.13g/100g), tryptophan (1.26g/100g). Proximate composition shows that the protein content of lima bean-benniseed food (8.33%) and lima bean porridge (8.30%) were significantly (P<0.05) higher than lima bean-hungry rice food while lima bean-benniseed food had higher content of crude fat (13.46%), ash (2.28%) and crude fibre (4.09%) compared to other foods. The carbohydrate content (24.58%) of lima bean porridge was significantly (P<0.05) higher than other foods. The study shows that lima bean foods have a good nutritional profile therefore; increase in the consumption of foods prepared with lima beans could serve as an addition to food-based strategies used in decreasing malnutrition and its effects